1986
DOI: 10.1017/s0021859600063887
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the complete diet composition given during the winter period to an autumn-calving herd

Abstract: SUMMARYAutumn-calving cows on a complete diet system were given a similar amount of concentrates over two winter periods in the years 1980–1 and 1981–2. Two feed allocation systems were examined: step (different diets given at different stages of lactation) and uniform (one single diet given over all the winter period).The yield of fat-corrected milk (FCM) was similar (P > 0·05) in both systems with 5·32 and 5·37 t/cow for the step and uniform system respectively in the 1st year and 4·75 and 4·35 t/cow in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Results of our studies (Kroll & Owen, 1986) and many others have shown a greater yield persistency if one fixed diet is given (Johnson, 1977;Spahr, 1977;Broster, 1980) and also does not show any effect of diet distribution on milk yield and mainly FCM yield.…”
Section: Effect Of the Feeding System On Cows Of Different •Potentialsupporting
confidence: 63%
“…Results of our studies (Kroll & Owen, 1986) and many others have shown a greater yield persistency if one fixed diet is given (Johnson, 1977;Spahr, 1977;Broster, 1980) and also does not show any effect of diet distribution on milk yield and mainly FCM yield.…”
Section: Effect Of the Feeding System On Cows Of Different •Potentialsupporting
confidence: 63%
“…However, several experiments were found where a specific time relative to parturition or milk yield were used to assess the time for reducing ration energy concentration (e.g. Smith et al, 1978;Cassel et al, 1984;Kroll et al, 1986). Results from these experiments indicate, that the positive effect of high energy rations in early lactation was counterbalanced by reduced milk yield persistency when ration energy concentration was reduced.…”
Section: Danish Holsteinmentioning
confidence: 99%